The influence of valence and decision difficulty on self-referential processing - Meffert, Harma; Blanken, Laura; Blair, Karina S.; White, Stuart F.; Blair, James R. (Frontiers in Human Neuroscience, 2013)
Self-referential processing is defined as the process by which a person becomes aware that specific contents are related to his or her own self. Cortical midline structures, such as dorsal and medial prefrontal cortex, and regions such as inferior frontal cortex, insula and temporal pole have been implicated in self-referential processing. However, the specific contribution of each of these areas is still largely unknown. More particularly, not many studies have examined the influence of valence and decision making difficulty on regions involved in self-referential processing. In this study, participants evaluated how well personality traits, differing in valence and decision difficulty, described themselves or president Obama. In line with predictions, ventral, rostral and dorsal parts of medial prefrontal cortex showed greater activity when participants judged traits about themselves relative to judging traits about President Obama. However, none of these regions showed significant modulation by trait valence. Increasing trait decision difficulty was associated with increased activity within dorsal medial prefrontal cortex and bilateral anterior insula. However, there was very minimal overlap (6/119 voxels, i.e. 5%) of the regions of dorsal medial prefrontal cortex implicated in self-referential processing and those implicated in trait decision difficulty. The results are interpreted within current accounts of self-referential processing.